Advanced linear beam models to be exploited in the implicit corotational framework and FEM implementation - Genoese, Alessandra; Bartolino, Roberto; Casciaro, Raffaele; Garcea, Giovanni; Bilotta, Antonio (My University, 2012)
Università degli Studi della Calabria
Keywords: Scienza delle costruzioni; Modelli lineari; Travi